Revealing the Influence of Hafnium on the Microstructure, Corrosion, and Wear Properties of Fe-10Cr Alloy - Erol, Mahmut; Tarakci, Gurkan; Ozbay Kisasoz, Burcin; Bayrak, Yahya; Kisasoz, Alptekin (SPRINGER HEIDELBERG, 2026)
The study aimed to reveal the influence of hafnium addition on the characteristics of Fe-10Cr alloy. Fe-10Cr alloys containing varying hafnium additions (0-3 wt%) were fabricated by plasma arc melting to investigate the effect of hafnium on microstructural evolution, mechanical properties, wear behavior, and corrosion performance. Microstructural characterization was conducted using SEM, EDS, EBSD, and XRD techniques. The results indicated that low hafnium additions (0.5-1 wt%) led to grain coarsening due to insufficient heterogeneous nucleation, whereas higher hafnium contents (>= 2 wt%) promoted significant grain refinement through the formation of Hf-rich intermetallic phases, including Fe2Hf, FeHf2, and Cr2Hf. These intermetallic phases acted as effective heterogeneous nucleation sites and inhibited grain growth. The addition of hafnium resulted in reduced hardness and wear resistance, primarily attributed to the diminished solid-solution strengthening and increased microstructural heterogeneity caused by grain boundary segregation. In contrast, corrosion resistance improved markedly with increasing hafnium content, as demonstrated by a noble shift in corrosion potential, reduced corrosion current density, enhanced passivation behavior, and increased impedance response. The enhanced corrosion performance was attributed to the formation of stable and protective Hf-containing passive films, particularly in alloys containing 2 and 3 wt.% hafnium. Overall, the findings reveal a clear trade-off between hardness, wear performance, and corrosion resistance in Fe-Cr-Hf alloys, providing insights for tailoring alloy compositions for specific industrial applications.
Keywords: Fe-Cr-Hf alloy; Plasma arc melting; Electrochemical corrosion; Dry sliding wear; IRON-CHROMIUM ALLOYS; LAVES PHASE; MECHANICAL-PROPERTIES; HIGH-TEMPERATURE; PASSIVE FILM; CR; STEEL; HF; RESISTANCE; DEGRADATION; Science & Technology - Other Topics